IMPLIKASI PERNIKAHAN DINI TERHADAP KEHARMONISAN KELUARGA DI SUMBAWA - Edy Kurniawansyah; Ahmad Fauzan; Eni Tamalasari (Jurusan P. IPS, FKIP, Universitas Mataram, 2021)
ABSTRACTMarriage conduted at a young age is generally minimal in both physical and mental readiness, in addition it is feared that it will produce poor offspring. This is not only produced from undercooked seeds but also due to the couple’s lack of knowledge about how to minimize emotions and build a harmonious family. Early marriage in terms of psychology has risks such as being cut off from education, loss of job opportunites, young people to divorce, children lacking attention and deviations in behavior.Marriage conducted as a young a teenager is theoretically very prone toproblems because adolescents are still very unstable in their actions, because emotions in adolescents are not yet fully formed. Teenage emotionality is between the emotionality of children and adults. So that the formulation of the problem inthis study is a qualitative method with a desvriptive approach that aims to systematically and accurately describe facts and characteristic about the population or regarding a particular field with observation, interview and documentation techniques. The results of this study indicate that the implications of early marriage or underage marriage are merried coupels who cannot marry or do not know their rights and obligations as husband and wife, this arises because of their physicalnor mental immature who tend to both have selfishnessheight, besides that it also creates a bad influence on her children. For women who have early marriages will experience disorders in the womb that can endanger the health of the child and even children born will tend to be small and thin. It will also have an adverse effect on each family.